Effect of Intermediate-Frequency Repetitive Transcranial Magnetic Stimulation on Recovery following Traumatic Brain Injury in Rats. (29th November 2017) - Verdugo-Diaz, Leticia; Estrada-Rojo, Francisco; Garcia-Espinoza, Aron; Hernandez-Lopez, Eduardo; Hernandez-Chavez, Alejandro; Guzman-Uribe, Carlos; Martinez-Vargas, Marina; Perez-Arredondo, Adan; Calvario, Tomas; Elias-Viñas, David; Navarro, Luz
Abstract : Traumatic brain injury (TBI) represents a significant public health concern and has been associated with high rates of morbidity and mortality. Although several research groups have proposed the use of repetitive transcranial magnetic stimulation (rTMS) to enhance neuroprotection and recovery in patients with TBI, few studies have obtained sufficient evidence regarding its effects in this population. Therefore, we aimed to analyze the effect of intermediate-frequency rTMS (2 Hz) on behavioral and histological recovery following TBI in rats. Male Wistar rats were divided into six groups: three groups without TBI (no manipulation, movement restriction plus sham rTMS, and movement restriction plus rTMS) and three groups subjected to TBI (TBI only, TBI plus movement restriction and sham rTMS, and TBI plus movement restriction and rTMS). The movement restriction groups were included so that rTMS could be applied without anesthesia. Our results indicate that the restriction of movement and sham rTMS per se promotes recovery, as measured using a neurobehavioral scale, although rTMS was associated with faster and superior recovery. We also observed that TBI caused alterations in the CA1 and CA3 subregions of the hippocampus, which are partly restored by movement restriction and rTMS. Our findings indicated that movement restriction prevents damage caused by TBI and that intermediate-frequency rTMS promotes behavioral and histologic recovery after TBI.